The impact of parents' education and attending vocational high school to college entrance - Wahyudi Wicaksono; Robert A. Sparrow; Peter van Bergeijk (Jurnal Pendidikan Vokasi, 2018)
Using IFLS data 2007 and 2014, this study aims to examine the impact of parents' education and attending vocational high school to the probability of children attending tertiary education. This study is motivated by the government plan in increasing the proportion of vocational high school graduates compare to general high school graduates. Multinomial-Logit model is used to examine the senior high school types, Logit and Probit are used to examine the decision on pursuing tertiary education. The main conclusions are (1)  parents' education has significant impact on the children's senior high school preference and college enrollment, (2) children who attended vocational senior high school have a lower probability to enrol in tertiary education compared to those who attended general senior high school or MA